Phytochemical screnning, antioxidant and antibacterial activities of averrhoa blimbi fruit extract and leucaena leucocephala leaves extract on common skin bacteria / Siti Aishah Sabani Tajudin - Tajudin, Siti Aishah Sabani (2020)
Averrhoa bilimbi and Leucaena leucocephala are medicinal plants that have several benefits like antibacterial, antifungal, anti-inflammatory and antidiabetic. The main purpose of this study is to examine the antibacterial activities of Averrhoa bilimbi fruitsand Leucaena leucocephala leaves methanolic extract by Kirby-Bauer Disk Diffusion Method towards common skin bacteria, which are Propionibacterium acnes, Staphylococcus aureus and Pseudomonas aeruginosa. Besides, this study also has the purpose to evaluate the antioxidant properties by DPPH assay and identify the compound in both plants by phytochemical analysis using GC-MS. Kirby-Bauer Disc Diffusion Method was used in carrying out antibacterial testing of A. bilimbi fruits and L.leucocephala leaves extracts. The results showed that all the bacteria were susceptible towards A. Bilimbi fruits extract while only P. aeruginosa and S. aureus were susceptible towards L. leucocephala leaves extract. Meanwhile, antioxidant activities that have been examined using DPPH assay resulted in high antioxidant activities with 90.4% for A.bilimbi and 99.1% for L. leucocephala at 100 mg/mL concentration. Other than that, chemical components of methanolic extract of both plants have been examined by using GC-MS phytochemical analysis. The result obtained from the analysis of A. bilimbi crude fruits extract showed the presence of compounds of 5(Hydroxymethyl) furan-2-carbaldehyd, 9-Undecenal,2,10-dimethyl and vaccenic acid which contributed to antibacterial activity and also n-Hexadecanoic acid that contributed to antioxidant activity. While in L. leucocephala leaves extract, compounds of n-Hexadecanoic acid which has antioxidant property has been found. To conclude, A. bilimbi and L.leucocephala have shown a great ability as antibacterial and antioxidant agents and have potential to be used in natural skin treatment.